1993
DOI: 10.1177/095148489300600206
|View full text |Cite
|
Sign up to set email alerts
|

A Task Contingent Model of Medical Practice Organization

Abstract: The treatment of acute episodes of morbidities in hospitalized patients is a complex and uncertain task. To accomplish this task, physicians organize themselves into teams in an effort to overcome two constraints: the necessity to offer both complete care and continuous care. This study examines the extent to which the nature and size of medical teams is explained by task difficulty and task variability, which are two dimensions of task uncertainty. The results support globally the hypothesis that the organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The analysis level is shifted from the individual to the group, and the group is perceived as a contingency that may hamper coordination in clinical decision-making and explain variations in clinical resource utilization. To our knowledge, although work-group dimensions are common in organizational studies, there is only one study that speci®cally analysed this aspect of medical care organization as a constraint which might explain medical practice variations (Sicotte et al, 1993a;1993b). This study suggested that medical work-group practice did not entirely overcome the coordination problems inherent in task interdependence and was in itself a factor explaining variations in use.…”
Section: Previous Researchmentioning
confidence: 95%
See 1 more Smart Citation
“…The analysis level is shifted from the individual to the group, and the group is perceived as a contingency that may hamper coordination in clinical decision-making and explain variations in clinical resource utilization. To our knowledge, although work-group dimensions are common in organizational studies, there is only one study that speci®cally analysed this aspect of medical care organization as a constraint which might explain medical practice variations (Sicotte et al, 1993a;1993b). This study suggested that medical work-group practice did not entirely overcome the coordination problems inherent in task interdependence and was in itself a factor explaining variations in use.…”
Section: Previous Researchmentioning
confidence: 95%
“…Contingency theory research suggests that task complexity is a function of two constructs Ð task dif®culty and task variability. It also suggests that each of these constructs has a unique relationship with organizational design (Fry and Slocum, 1984;Perrow, 1967;Sicotte et al, 1993b;Van de Ven and Delbecq, 1974;Whithey et al, 1983). Task dif®culty refers to the ability to analyse the task itself Ð the degree of complexity of the decision-making process in performing the task, the amount of thinking time required to solve task-related problems, and the body of knowledge that provides guidelines for performing the task.…”
Section: Task Characteristicsmentioning
confidence: 99%
“…The analysis level is shifted from the individual to the group, and the group is perceived as a contingency that may hamper coordination in clinical decision-making and explain variations in clinical resource utilization. To our knowledge, although work-group dimensions are common in organizational studies, there is only one study that specifically analysed this aspect of medical care organization as a constraint which might explain medical practice variations (Sicotte et al, 1993a;1993b). This study suggested that medical work-group practice did not entirely overcome the coordination problems inherent in task interdependence and was in itself a factor explaining variations in use.…”
Section: Previous Researchmentioning
confidence: 97%
“…Contingency theory research suggests that task complexity is a function of two constructs -task difficulty and task variability. It also suggests that each of these constructs has a unique relationship with organizational design (Fry and Slocum, 1984;Perrow, 1967;Sicotte et al, 1993b;Van de Ven and Delbecq, 1974;Whithey et al, 1983). Task difficulty refers to the ability to analyse the task itself-the degree of complexity of the decision-making process in performing the task, the amount of thinking time required to solve task-related problems, and the body of knowledge that provides guidelines for performing the task.…”
Section: Task Characteristicsmentioning
confidence: 99%
“…On one hand, more clinician affiliations across hospitals may increase coordination problems and limit clinician availability to patients, inducing multihospital clinicians to compensate for the lack of continuity in care by engaging in defensive medicine and by increasing their reliance on diagnostic tests and support staff rather than thorough patient examination. 12,13,15 Greater use of hospital resources may then lead to increased costs. 1 On the other hand, more hospital affiliations may improve care and lower costs by facilitating the transmission of new medical knowledge, best-care practices, and greater access to electronic health records.…”
Section: Introductionmentioning
confidence: 99%